Thermal performance evaluation of solar tunnel greenhouse dryer for drying amla candy - Patil, Rajendra; Suryawanshi, Dinesh; Kulkarni, Yogesh; Pardeshi, Sagar (Journal of Postharvest Technology, 2022)
Adequate and sophisticated postharvest processing method plays a significant role in minimizing the losses of harvested vegetables and fruits. The amla is a seasonable fruit and has a storage life of only 3-4 days after harvesting due to high moisture content. Hence, there is a need to preserve the amla fruit through controlled drying for a non-seasonal requirement. In this study, a forced convective solar tunnel greenhouse dryer is proposed for the dehydration of amla candy. The thermodynamic concert of the dryer and behaviour of drying air was investigated in terms of various performance indicators by the first law of thermodynamics. During experimentation, the dryer efficiency was estimated at 3-21%, whereas the pickup efficiency was found at 20-63%. It was observed that the amla candy samples satisfactorily dried in the range of 38-600C drying air temperature and 18-31% relative humidity, at 2-4m/s of drying air velocity. The specific moisture extraction ratio and heat utilization factor varied between 0.04 -0.30 kg/kWh & 0.18-0.70, respectively. Results indicate that the energy exploitation and energy utilization ratio decreased along drying time. The thermal analysis revealed that the dryer took only 35 hours to dry amla candy, whereas 48 hours were needed for open sun drying. The effect of thickness and pretreatment on amla candy was also examined. The quality of dried amla candy was found to be excellent in colour, appearance & taste than open sun drying. It is hoped that this study may be valuable in reducing postharvest loss of amla fruit.